Evaluation of the role of village government in handling of stunting policy in Surakarta - Shafira Sukma Anggreani; Kusuma Estu Werdani (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Stunting is one of the nutritional problems in toddlers that has become a global concern. Stunting is a chronic nutritional problem due to a lack of nutritional intake over a long period characterized by height that is not by age, which occurs in toddlers. Surakarta City is one of the areas that ranks 17 out of 35 districts/cities in the Central Java Province with the highest stunting prevalence rate of 20,4% in 2021. Based on the survey results, it was determined that the health center with the highest number of stunting cases in Surakarta City is Pajang Health Center, with 187 stunting children. Village governments are required to participate actively in dealing with stunting. However, several regions in Indonesia still have problems in dealing with stunting cases. Purpose: To analyze the role of village government in the Pajang Village area in handling stunting policy. Method: This study was qualitative. The informants were selected using purposive sampling. They were divided into two groups: primary informants and triangulation informants. The main informants were the Midwife, Nutritionist, integrated service post chairman of work program 4 family empowerment and welfare. The triangulation informants were The Head of the Village and The Village Secretary. Results: Based on Ryaas Rasyid's Theory, this study's results show that the village government's role as a regulator, denominator, and facilitator has been implemented well and optimally, but there are obstacles to budget allocation related to stunting. Conclusion: The role of the government as a regulator has been running well, as seen from the optimal planning, implementation, and evaluation in handling stunting. The role of the government as a denominator is seen in providing education and training to nutritionists, cadres, and the community. Meanwhile, the role of the government as a facilitator has not been running optimally because there are still obstacles in managing the budget related to stunting and the lack of facilities provided by the village government.